Models of Strategic Innovation Management in the Context of Ensuring the Competitiveness of Grain Market Enterprises - Sedikov Denys V. (Problemi Ekonomiki)
The article highlights the theoretical foundations and practical aspects of strategic innovation management in the context of enhancing the competitiveness of grain market enterprises. Key models of innovation management are considered, primarily the Henderson – Clark model, which classifies innovations based on the level of changes in components and product architecture, the conception of open innovation by H. Chesbrough, which involves engaging external partners and ideas, as well as the model of disruptive innovations by C. Christensen, capable of significantly transforming the market. Based on a review of recent research, it is emphasized that the implementation of these models contributes to the flexible adaptation of agricultural enterprises to a dynamic environment, allows for cost optimization, increases yield, and forms long-term competitive advantages. The experience of leading Ukrainian agroholdings (MHP, Kernel) has been analyzed, which combine incremental (gradual) and radical (breakthrough) innovation strategies, apply formalized mechanisms for idea generation and selection, and implement digital technologies to create a unified information space. It is demonstrated that the development of open innovations, particularly through partnerships with scientific institutions and startups, is a significant factor in accelerating the innovation process and overcoming the risks inherent in agricultural production. An adapted model of strategic innovation management has been studied, which takes into account the seasonality of the agrarian cycle, the high capital intensity of technologies, and the need for continuous improvement of agro-technical solutions. The application of such an approach allows grain market enterprises to increase production efficiency while minimizing production and market risks.